Time to achieve first blood pressure control after diagnosis among hypertensive patients at primary health care clinics: a preliminary study - Cheong, Ai Theng; Md Said, Salmiah; Muksan, Norliza (Sage Publications, 2015)
This study aimed to examine the duration to achieve first blood pressure (BP) control after the diagnosis of hypertension. This was a retrospective cohort study on 195 hypertensive patients’ (age ≥18 years) records from a primary health care clinic. The median time to achieve first BP control was 7.2 months (95% confidence interval [CI] = 4.99-9.35). Cox proportional hazards regression results showed female patients were 1.5 times more likely to achieve BP control when compared with male patients (hazard ratio [HR] = 1.50, 95% CI 1.09-2.09, P = .013). Those with monotherapy were 2 times more likely (HR = 2.09, 95% CI = 1.39-3.13, P < 0.001) and those on 2 drugs were 3.5 times more likely (HR = 3.49, 95% CI = 1.65-7.40, P = .001) to achieve BP control than those with nonpharmacological treatment. The median time to achieve BP control was longer than the recommended time. Doctors may need to consider starting the pharmacological treatment early and be more aggressive in hypertensive management for male patients.